Dynamics of the Protracted Chieftaincy Conflict in Nkwanta of the Oti Region of Ghana - David Suaka Yaro; Daniel Dramani Kipo-Sunyehzi; Gregory Titigah (Eastern African Journal of Humanities and Social Sciences)
The study examines the dynamics of the Nkwanta conflict from the lens of the causes, the effects of the conflict, and the measures that militate against the management of the protracted conflict in the Oti Region of Ghana. It draws the theoretical insights from Azar’s “extended societal conflicts" which postulates that conflicts or disputes in society are because of interlinked networks of insufficient development, structural deficiencies, and divisions in identity among other factors. The study utilizes largely a qualitative research design in which 23 interviewees shared their views, opinions, and perspectives on the Nkwanta conflict in the Oti Region of Ghana. The Nkwanta area is also closer to the Togo border which makes the area strategic and could make the conflict have a spill-over effect on Ghana and Togo due to the close ethnic relations of the Nkwanta people of Ghana and those in Togo. The study found that chieftaincy and land ownership are the main causes of the conflict. Other factors that contribute to the conflict include partisan politics and the vested interest of some individuals in the area. In terms of the effects of the conflict loss of lives and properties are the main effects while effective conflict resolution stems from the involvement of all the parties through respect, compromise, and forgiveness from the parties involved in the conflict. The study recommends the involvement of unbiased external mediators with a high sense of professionalism toward the resolution of the protracted Nkwanta conflict in the Oti Region of Ghana.